IMPACT OF TECHNOLOGICAL CAPABILITIES, DESIGN INNOVATION, AND OPERATIONS ON THE PERFORMANCE OF SMALL AND MEDIUM TEXTILE ENTERPRISES IN GHANA - Abraham, Isaac; Mensah, Christiana Konamah Okai-; Howard, Ebenezer Kofi; Asinyo, Benjamin Kwablah (International Journal of Small and Medium Enterprises, 2023)
Many developing countries, especially those in sub-Saharan Africa, struggle with design innovation as a result of a lack of infrastructure, skilled labour, and financial constraint, hindering their ability to compete in the global economy. The study investigates the effect of technological capabilities, design innovation, and operations on the performance of Small and Medium Textile Enterprises (SMTEs) in Ghana filling the knowledge gap and contributing to economic development in the region. A quantitative approach was employed, and data were obtained from 80 SMTEs using a self-administered questionnaire. The results show that there is a significant correlation between technological capabilities and the performance of SMTEs, indicating that current technologies are making textile companies more productive and efficient, resulting in improved performance. The study also found that technological capabilities positively influence design innovation practices, which, in turn, positively relate to the performance of the enterprise. Moreover, there is a positive relationship between the technological capabilities and operations of the enterprises. The findings of the study are consistent with previous research and suggest that enterprises that invest in the appropriate technology can improve their design innovation, operations, and overall performance. The study recommends that SMTEs in Ghana must invest in technological capabilities that are suitable for their business needs to improve their operations, design innovation, and overall performance. Additionally, policymakers should provide adequate support to SMTEs to enhance their technological capabilities, design innovation, and operations through funding, training, and infrastructure development. JEL Classification Codes: O32, E22, D02, L25, L67.